EFEKTIVITAS KONSELING KELOMPOK DENGAN PENDEKATAN REBT(RATIONAL EMOTIVE BEHAVIOR THERAPY) DALAM MENGURANGI KECEMASAN ATLET PENCAK SILAT - Alfiah Mangestuti Alfi; Drajat Edy Kurniawan (Advice: Jurnal Bimbingan dan Konseling, 2025)
The purpose of this study is to test the effectiveness of group counseling with the REBT approach in reducing anxiety in pencak silat athletes. The method used in this study is a quantitative experiment with a one group pretest posttest design. Based on interviews and observations, there are several pencak silat athletes who experience excessive anxiety. Data collection for this study used a questionnaire. The population in this study were all seventh grade students at Muhammadiyah 1 Seyegan Junior High School. The subjects of this study were taken based on the results of pre-research observations and interviews, so sampling used purposive sampling with data collection using a pencak silat athlete anxiety questionnaire that will be taken from 6 athletes with the highest anxiety. The data analysis technique used a non-parametric test with the Kruskall Wallist test method. The results of this study indicate that group counseling with the REBT approach is effective in reducing anxiety in pencak silat athletes, this is evidenced by the results of the Kruskall Wallist test with a probability value of sig. (2-tailed) 0.004 <0.05. As well as the difference in the average score of the pencak silat athlete anxiety questionnaire of 28.4 from the pretest and posttest results.